Pain perception and motivation in football players: neuroscience contributions - Martinez, Victor Matheus Lopes (2022)
This article is about a bibliographic review about the perception of pain and how it affects motivation and psychological states in football players. For this, a narrative research of bibliographic nature was carried out using the electronic databases PubMed, Scielo and Capes. The general objective of this study was to identify the relationship between pain perception and motivation in football players. With the results, it was realized that, even in pain, athletes, in cases of enduring it, avoid informing the technical committee for fear of being left out of the squad (losing title and relevance). In addition, athletes are very affected in motivation, especially with regard to psychological factors in times of injury, reaching cases of depression and stress when they are away for long periods. It is concluded, then, that the athletes are mostly intrinsically motivated. The coach, as well as his methodologies, are the main factors of extrinsic motivation The subjective exacerbated perception of pain is one of the demotivational factors, mainly in cases of injuries, which occurs due to the heroic character that is created around the athlete and the competitive high rate of revenue collection. Precisely for this reason, psychological monitoring must be carried out with these players, both from larger and smaller divisions, seeking to always help them, not only in times of injury. It is also suggested that further studies be conducted in the area for a better understanding of the studied phenomenon.